Implementasi Penggunaan E-Tilang Terhadap Pelanggaran Lalu Lintas Di Polresta Barelang Kota Batam - Dwi Utari Khairun Nisa; Jamhur Poti; Okparizan Okparizan (Universitas Sains dan Teknologi Komputer, 2023)
In Batam City, traffic violations often occur, hence the implementation of E-tickets. The purpose of this research is to find out the implementation of E-Tilang program in handling traffic problems in Batam City. This research is a descriptive research with a qualitative approach. Data collection techniques through observation, interviews and documentation. This research uses 6 indicators from Van Meter and Van Horn’s theory. The results of the research a) The standards and objectives of the E-tickets policy make it easier for the public to pay and make it easier not to attend the trial. B) For resources, they have received training on the application of E-tickets so that officers understand its application, but the problem lies in technological resources where access is slow c) For the characteristics of the implementing agency, they have followed the SOP while carrying out their duties. D) Communication, police communication with the court. D) Communication, police communication with the court is quite good, but socialization between the police and the community is not optimal because there are still people who do not know the E-ticket policy. E) Implementers’ attitudes, the responses of officers and the public support its implementation because E-tickets make it easier for the public and officers in the field. F) Economic, Social and Political Conditions. The economic condition of the community is not enough to affect the ticket fines imposed on the community. Social conditions, the level of violations in Batam is quite good with the existence of E-tickets, in line with the large enough fines so that people start to be deterred.